Justification of regional development of industrial enterprises in the plane of their financial support: experience of Ukraine - Dedilova, Tetiana; Levchenko, Iaroslava; Nosyriev, Oleksandr; Osypova, Svitlana (Technology center PC, 2021)
The object of research is the regional industry of Ukraine. In the sectoral context, the general structure of the regional industry is significantly deformed, and the strategic and sectoral guidelines of economic policy are blurred, which makes it difficult to restore the economic growth of the country as a whole. The industrial potential is concentrated mainly in traditional industrial regions. The development of industry is hampered by the wornout state of the technical and technological base of production, a high level of staff turnover, an insignificant percentage of the production of high-tech products, a lack of institutions for innovative development, and similar factors. The complexity of the procedures for financing the processes of industrial development is mediated by the innovative activity of its subjects. The processing industry is the central center of innovation in the industry. Among the sources of financing for innovations, enterprises’ own funds prevail. It is substantiated that the main directions of regional development of industrial enterprises in terms of financial support for their functioning are support and encouragement of innovation, measures to increase the competitiveness of industrial products, internationalization and support for exports. It is proved that the regions of the country unevenly use the mechanisms of investment support for industry, depending on the characteristics of the development of the regional economy. This necessitates the creation of investment mechanisms aimed at ensuring the management of the competitiveness of regional industrial complexes on the basis of the development and implementation of innovations. A multichannel investment mechanism has been proposed to ensure a full-fledged infusion of financial resources from several sources as an effective tool for financial influence on the development of industrial enterprises. It is noted that among the directions of development of industrial management should remain both traditional measures to support domestic producers (state regional purchases) and alternative (financial leasing, initial placement of securities, joint investment). For a separate direction of industrial development, it is recommended that state support of cluster interregional initiatives based on the use of leading European experience. The highlighted areas are relevant for potential foreign partners who intend to carry out joint business with Ukrainian industrial enterprises. Also, the indicated research results are significant in the process of attracting investments at the regional level and have practical value for foreign investors when they consider a portfolio of alternatives to foreign direct investment in Ukrainian industrial facilities.
Keywords: industrial enterprise; industrial policy; regional industry of Ukraine; financial resources; innovative development